What types of diversity benefit workers? Empirical evidence on the effects of co-worker dissimilarity on the performance of employees - Fidan Ana Kurtulus (University of Massachusetts, Department of Economics, 2011)
This paper explores the consequences of grouping workers into diverse divisions on the performance of employees using a dataset containing the detailed personnel records of a large U.S. firm from 1989-1994. In particular, I examine the effects of demographic dissimilarity among co-workers, namely differences in age, gender and race among employees who work together within divisions, and non-demographic dissimilarity, namely differences in education, work function, firm tenure, division tenure, performance and wages among employees within divisions. I find evidence that age dissimilarity, dissimilarity in firm tenure, and performance dissimilarity are associated with lower worker performance, while wage differences are associated with higher worker performance. My analysis also reveals that the effects of certain types of dissimilarities get smaller in magnitude the longer a worker is a part of a division. Finally, the paper provides evidence that the relationships between performance and the various measures of dissimilarity vary by occupational area and division size.
Keywords: D2; J1; J2; J3; J8; L2; M5; 330; Work-Group Diversity; Communication Costs; Knowledge Spillovers; Specialization; Worker Performance